SPINAL CORD-SUBARACHNOID SPACE RATIO AT CERVICAL REGION IN NORMAL THAI PEOPLE. - METARUGCHEEP, Pichest (The ASEAN Journal of Radiology, 2023)
Measurement of transverse diameter of cervical cord & subarachnoid space between C4-C6 region was performed. The ratio between them was analysed in 160 cases of patients suffering from low back without neck symptom and submitted to water soluble myelogram. The normal spinal cord — subarachnoid space ratio (C/SAS) is in the range of 0.57-0.79, mean is 0.67 and SD 0.046. This can be used as the indicater of abnormal size of the spinal cord in myelographic interpretation if the ratio is under 0.57 or above 0.77. (mean + 2SD.)